مناهج كامبريدج للرياضيات في ضوء الاقتصاد القائم على المعرفة من وجهة نظر المعلمين في سلطنة عمان واتجاهاتهم نحوها - خروصي، عيسى خميس علي
This study explores teachers’ perceptions of the Cambridge Mathematics curriculum in reference to the knowledge-based economy in the Sultanate of Oman. It aims to identify the effect of these attitudes on the relationship between the perceptions towards the curriculum and its application. To achieve the study aims, the researcher used a relational descriptive methodology and designed a questionnaire with 41 items covering three topics: teachers' perceptions, teachers' attitudes, and implementation and application of the curriculum. The questionnaire was applied to a sample of 312 male and female mathematics teachers. The main data analysis was conducted by modeling the structural equations using Amos (Version 25). In addition, interviews were conducted with seven teachers and combined with the scale results. The result reflected a high level of teachers' perceptions on the content of the Cambridge Mathematics curriculum for grades 5–6 and a high level of positive attitudes towards them. The results also indicated that the teachers’ level of implementation and application was high. The result suggests that there is direct and positive relation between the level of teachers' perceptions towards the curriculum, the level of their application, and their attitudes towards it. The result also reveals a direct relationship between attitude, implementation, and application. The study recommends further research into the perception and application of the curriculum taught in local public schools. The current curriculum should be amended based on the teachers’ experiences in the classroom as it has a direct effect on their performance and their ability to implement it .